Desenvolvimento e validação de método analítico espectrofotométrico para quantificação de nerolidol em um dispositivo polimérico de liberação prolongada, após derivatização com vanilina - Ribeiro, Tatiana Gomes; Franca, Juçara Ribeiro; Marques, André Mesquita; Coelho Kaplan, Maria Auxiliadora; Faraco, André Augusto Gomes; Castilho, Rachel Oliveira (Eclética Química, 2014)
This work describes the development and validation of analytical method to assay nerolidol in a hydrophilic matrix of quitosan by UV/visible spectroscopy. The method is based on the formation of purple derivative between nerolidol and vanillin. The validated method was linear (2.5 - 50 mg mL-1, concentration range, r > 0.99), precise (RSD 0.44% for repeatability and 0.32% for intermediate precision), accurate (100.04% recovery), robust and specific. Detection and quantitation limits were 0.74 mg mL-1 and 2.26 mg mL-1, respectively. The method is simple and fast and it was applied successfully. Alternatively, the described method may be applied for the analysis of alcohols and unsaturated lipids.